Tracking mitochondrial pH fluctuation during cell apoptosis with two-photon phosphorescent iridium(iii) complexes. Issue 19 (19th February 2018) - Qiu, Kangqiang; Ke, Libing; Zhang, Xuepeng; Liu, Yukang; Rees, Thomas W.; Ji, Liangnian; Diao, Jiajie; Chao, Hui
Abstract : Two-photon phosphorescent Ir(iii ) complexes containing two morpholine moieties were developed for monitoring the mitochondrial pH fluctuation during apoptosis. Abstract : Two iridium(iii ) complexes with ligands containing morpholine groups were used to track mitochondrial pH fluctuation during cell apoptosis as their emissive intensities linearly increased with increase in pH values.